Advancing Sustainability via the Development of the Modified Environmental, Social and Governance Disclosure Index (MESGi) for Malaysian Public Listed Companies - Monie Ramba; Corina Joseph; Roshima Said (International Journal of Supply Chain Management, 2018)
The paper aims to explain the development of the modified environmental, social governance disclosure index (MESGi) for the Malaysian public listed companies. MESGi consists of 130 items will serve as a holistic and comprehensive checklist to evaluate the extent of environmental, social and governance information disclosure on companies annual and sustainability reports. It is hoped that the MESGi would enhance the level of disclosure by companies as the checklist includes both local and international items that have been developed in a detailed process. As well, it is hoped that the MESGi would assist more Malaysian companies to be listed in the FTSE4Good Index. This would in turn assist in advancing the sustainability agenda in the Malaysian business environment.